2017
DOI: 10.3389/fmicb.2017.00632
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Metagenomic Understanding on the Bacterial Composition and Resistome in Hong Kong Banknotes

Abstract: Currency is possibly one of the main media transmitting pathogens and drug resistance due to its wide circulation in daily life. In this study, we made a comprehensive characterization of the bacterial community present on banknotes collected from different geographical regions of Hong Kong (HK) by performing in vitro characterization of the bacterial presence and resistome profile, as well as metagenomic analysis including microbial diversity, the prevalence of potential pathogens, the dissemination potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
2
21
0
1
Order By: Relevance
“…Our results revealed a similar but more comprehensive scenario about the increased HGT potential under antibiotic treatment, supporting the hypothesis that antibiotic pressure could drive the dissemination of the resistome [16]. According to the definition of HGT potential, the overall increase of ARGs abundance could be the major reason for the overall increased HGT potential, although the increased ARG abundance may neither guarantee an increased HGT potential (see Methods), nor is it proportionate to overall increased abundance [24]. More importantly, we observed that the increased HGT potential of ARGs was compounded by antibiotic selection of these genes at the single nucleotide level, highlighting the association between evolutionary plasticity and the horizontal transfer of ARGs [29].…”
Section: Discussionsupporting
confidence: 80%
“…Our results revealed a similar but more comprehensive scenario about the increased HGT potential under antibiotic treatment, supporting the hypothesis that antibiotic pressure could drive the dissemination of the resistome [16]. According to the definition of HGT potential, the overall increase of ARGs abundance could be the major reason for the overall increased HGT potential, although the increased ARG abundance may neither guarantee an increased HGT potential (see Methods), nor is it proportionate to overall increased abundance [24]. More importantly, we observed that the increased HGT potential of ARGs was compounded by antibiotic selection of these genes at the single nucleotide level, highlighting the association between evolutionary plasticity and the horizontal transfer of ARGs [29].…”
Section: Discussionsupporting
confidence: 80%
“…Most directly and urgently, the reported method represents a potential standard to aid wider and improved monitoring for awareness and control of microbial transmission in the global effort against healthcare associated infections and emerging infectious diseases. [21][22][23][24] With increased application of any method there comes a growing role for some form of standardization. Microbiomics methods are now supporting research, development, and clinical studies of traditional and new treatments including personalized medicine, [25][26][27] as well as an expanding list of non-medical areas of research and commerce, such as oceanography, agriculture, soil sciences and plant pathology to list but a few examples.…”
Section: Resultsmentioning
confidence: 99%
“…Methicillin resistance is an important consideration in all Staphylococcus spp., especially S. aureus. Global transmission of MRSA has been the subject of many studies [3,22]. In recent study, it was determined moniae, and Proteus mirabilis have demonstrated acquisition of plasmids secreting ESBL [28].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that contaminated fomites in general and paper currency in particular, plays a key role in the spread of bacterial infections with antimicrobial resistance [2,3,25]. Heshiki et al [22] in a metagenomic study showed that the antimicrobial resistance genes on banknotes were significantly higher (4.86 times more) than environmental samples such as water, air, soil and dust.…”
Section: B) Molecular Detection Of Ses Pvl and Tsst -1 Genesmentioning
confidence: 99%